2009
DOI: 10.1097/prs.0b013e3181b454d8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Genetic Factors Associated with Congenital Microtia: A Case-Control Study in Jiangsu, China, 2004 to 2007

Abstract: The results suggested that both environmental and genetic factors contribute to congenital microtia. The Gsc gene and the BMP5 maternal peptide gene may act as the predisposing genes of microtia. Further research is needed to clarify the relationship between the risk factors and microtia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 36 publications
5
40
1
Order By: Relevance
“…Residency area was identified as a factor affecting the development of microtia using the multivariate logistic analysis. The results of the present study are consistent with the results of Zhang et al, suggesting that education regarding prenatal care targeting rural area residents may be necessary [21].…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…Residency area was identified as a factor affecting the development of microtia using the multivariate logistic analysis. The results of the present study are consistent with the results of Zhang et al, suggesting that education regarding prenatal care targeting rural area residents may be necessary [21].…”
Section: Discussionsupporting
confidence: 96%
“…When pregnant women are exposed to toxins, including medications, or disease, fetal development can be affected and may eventually lead to congenital anomalies, such as microtia or anotia. In this study, disease during pregnancy, disease during the first trimester, medication use during pregnancy, and medication use during the first trimester had a significant effect on the occurrence of microtia, consistent with the results of Zhang et al [21]. However, the drugs used were diverse, including antibiotics, pain-killers, antipyretics and steroids and specific kinds of drugs could not be investigated because of subject's poor memories.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, environmental factors are considered as one risk factor for sporadic and isolated microtia. A number of studies have found that ethnicity, altitude, gestational exposure to alcohol, cigarette, inflammation, maternal diabetes, chemical exposure, influenza virus or medications can be associated with isolated microtia [19][20][21][22][23]. In this study, women who presented with cold-like syndrome were at higher risk for microtia as well as those that had the history of spontaneous abortion, which is similar to other studies [21].…”
Section: Discussionsupporting
confidence: 92%
“…Chemical exposure has been considered to be one risk factor for human deformities [22]. In our study, 14.3% of patients with microtia had been exposed to chemicals, such as paint, rubber, galena, pesticides or gasoline.…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary and environmental factors contribute to the pathogenesis of microtia. 1 Microtia is often accompanied by hemifaical hypoplasia, congenital heart disease, cleft lip and upper limb deformity. Microtia is also associated with many syndromes, such as first and second branchial arch syndrome, Oculoauriculovertebral Spectrum (OAVS, Goldenhar syndrome), Treacher-Collins syndrome, Nager syndrome, DiGeorge syndrome, CHARGE syndrome, Klippel-Feil syndrome and Meier-Gorlin syndrome.…”
Section: Dear Sirmentioning
confidence: 99%